A new species of Hypopygus Hoedeman (Gymnotiformes: Rhamphichthyidae) from the rio Trombetas system, Amazon basin, Brazil - Campos-Da-Paz, Ricardo (Zootaxa, 2018)
A new Hypopygus species is described from the igarapé Saracá, a stream in the lower rio Trombetas system, Pará State, Brazil. It differs from congeners by a unique combination of characters (either primitive or of uncertain polarity) which includes mouth position, interocular width, snout length, postorbital length, pectoral-fin length, snout-to-occiput length, caudal-filament length, counts of pectoral-fin rays and anal-fin rays, distribution of anal-fin chomatophores, as well as a set of osteological features. A phylogenetic analysis indicates that the new species, belongs to a monophyletic subgroup in Hypopygus that includes all congeners, except H. neblinae; its relationships within that clade, however, are currently uncertain, and a brief discussion is provided. Corrections are made concerning some morphometric and meristic information furnished in recent contributions regarding Hypopygus species.